2012
DOI: 10.5812/archcid.14410
|View full text |Cite
|
Sign up to set email alerts
|

HBV S Gene Premature Stop Codon in Strains From Middle Eastern Patients

Abstract: Background: We have previously reported on a premature stop codon in hepatitis B Virus (HBV) S gene among Iranian patients. This mutation may cause undetectable HBV by conventional ELISA methods. Objectives: In this study, we aimed to determine the presence of premature stop codon in HBV S gene from Middle Eastern countries with predominant HBV genotype D, subtype ayw2. Materials and Methods: Submitted HBV sequences to NCBI genome database from Middle Eastern countries (Iran, Iraq, Turkey, Pakistan, Afghanista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Ten genotypes (A to J) ( 3 , 4 ) and more than 30 subgenotypes ( 5 ) of HBV have been identified based on the general rule ( 6 ). These genotypes arise during replication as a result of nucleotide misincorporation, in the absence of any proofreading capacity by viral polymerases ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ten genotypes (A to J) ( 3 , 4 ) and more than 30 subgenotypes ( 5 ) of HBV have been identified based on the general rule ( 6 ). These genotypes arise during replication as a result of nucleotide misincorporation, in the absence of any proofreading capacity by viral polymerases ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16], Vazjalali et al, and Maleki et al [25,26], who have shown that increased frequency of A1762T/G1764A mutations accelerates disease progression. According to the results of our research, this mutation is more frequent in HBeAg-negative in the two-generation patient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in many countries have confirmed the presence of genotype D1 with subtype ayw2 [30]. Furthermore, there are many reports from the Middle East, indicating subtypes ayw2 and awy3 [28,31,32]. Also in Iran, this subtype has been reported in subgenotype D1 [28,29,33].…”
Section: оригинальные исследованияmentioning
confidence: 98%